Pemanfaatan Limbah Cangkang Kerang Untuk Produk Kerajinan Tangan Masyarakat Pesisir - Salim Abubakar; Masykhur Abdul Kadir; Rugaya H. Serosero; Riyadi Subur; Sri Endah Widiyanti; Adi Noman Susanto; Rina Rina; Reni Tyas Asrining P (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
The shellfish craft business is not only profitable for business actors, but also provides other benefits, including opening up employment opportunities for the community, increasing community creativity due to growing market demand and maintaining the product as a quality work of art. The output targets are household equipment (tissue boxes), interior accessories (wind chimes, door/window curtains) and souvenirs (key chains, brooches). Implementation methods include counseling, demonstration, training and coaching in the development of shellfish waste as a business opportunity. The training activity was successful because the enthusiasm of the participants was so great in pursuing the art of shellfish craft. Various forms of products and models produced are very varied. The products produced are tissue boxes, wind chimes, door/window curtains, key chains and brooches. The formation of a craft group “Creative Kastil” in the context of the sustainability of training activities.